2021
DOI: 10.1002/ctm2.424
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase JMJD1C promotes the polarization of M1 macrophages to prevent glioma by upregulating miR‐302a

Abstract: Glioma is regarded as an aggressive lethal primary brain tumor. Jumonji domain containing 1C (JMJD1C) is a H3K9 demethylase which participates in the progression of various tumors, but its specific function and underlying mechanism in glioma development remain undefined, which is the purpose of our work. We initially assessed JMJD1C expression in glioma tissues and cells using the assays of RT‐qPCR and immunohistochemistry. Meanwhile, the H3K9 level at the microRNA (miR)‐302a promoter region was measured by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…To demonstrate the utility of BipotentR using a different input pathway, we identified 14 bipotent TFCRs that simultaneously regulate angiogenesis and immune response (Supplementary Table S5) and 14 TFCRs that regulate evasion of growth suppressors and immune response (Supplementary Table S6), using these pathways as inputs to BipotentR (Methods). This included TBX21 and histone demethylase JMJD1C; whereas TBX21 is known to regulate angiogenesis and Tregs ( 101, 102 ), JMJD1C is known to regulate angiogenesis ( 103–105 ) and can polarize macrophages ( 106 ). We also evaluated bipotent targets for angiogenesis and growth suppressor evasion analogously as was done for immunometabolism targets.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the utility of BipotentR using a different input pathway, we identified 14 bipotent TFCRs that simultaneously regulate angiogenesis and immune response (Supplementary Table S5) and 14 TFCRs that regulate evasion of growth suppressors and immune response (Supplementary Table S6), using these pathways as inputs to BipotentR (Methods). This included TBX21 and histone demethylase JMJD1C; whereas TBX21 is known to regulate angiogenesis and Tregs ( 101, 102 ), JMJD1C is known to regulate angiogenesis ( 103–105 ) and can polarize macrophages ( 106 ). We also evaluated bipotent targets for angiogenesis and growth suppressor evasion analogously as was done for immunometabolism targets.…”
Section: Resultsmentioning
confidence: 99%
“…However, several contradictory studies have shown an antiproliferative effect of JMJD1C on cancer cells. For example, Zhong et al suggested that JMJD1C blocked cell growth by promoting M1 macrophage polarization in glioma [ 29 ]. We thought that the effect of JMJD1C on cell proliferation might be attributed to different pathological states.…”
Section: Discussionmentioning
confidence: 99%
“…Although JMJD1C (Histone demethylase) expression was low in gliomas, JMJD1C promoted demethylation of H3K9me1 at the promoter region of miR‐302a, which boosted miR‐302a expression. [ 69 ] miR‐302a suppressed the activity METTL3 that inhibited the SOCS2 expression via m 6 A modification. [ 69,70 ] As SOCS proteins intercepts interferon‐activated STAT‐mediated signaling, JMJD1C may regulate macrophage polarization by modulating STATs‐mediated signaling.…”
Section: Effect Of Ascorbic Acid On Monocyte Derived Dendritic Cells ...mentioning
confidence: 99%